Local Employment Growth in West Germany - A Dynamic Panel Approach - Uwe Blien; Jens Suedekum; Katja Wolf (European Regional Science Association (ERSA), 2005)
In times of high and persistent unemployment, it has become one of the most important policy tasks in many developed countries to trigger a process of sustained employment growth. An illustrative example is the policy of regional "growth-poles”, which assumes that a local concentration of a specific industry in a limited geographical area will lead to a growth take-off. The theoretical rationale for this type of regional policy can be knowledge spillovers, whose importance for the economic (employment) growth has been emphasised in the endogenous growth literature. Yet, there is a considerable debate about the precise nature of knowledge spillovers. Do the externalities accrue between sectors (Jacobs-externalities), or are they rather intra-sectoral (MAR-externalities)? Apart from the question what local economic structure is conducive for employment growth, an equally important issue concerns the timing of the impact of externalities. Is it the current economic structure that matters for employment growth, or rather the historical economic structure? If the former turns out to be the case, regional policies might become effective immediately. In the latter case the impact of policy might be slower but also longer lasting. In this paper we study the dynamics of local employment growth in West Germany from 1980 to 2001. Using dynamic panel techniques, we analyse the nature and the timing of Jacobs- and Marshall-Arrow-Romer externalities, as well as the impact of general human capital spillovers. Jacobs-externalities are stronger in manufacturing than in services, the opposite is true for MAR-externalities. General human capital spillovers are only found in manufacturing. The influence of all forms of externalities rapidly decays in time, suggesting that they are rather static than dynamic. Additionally, we look at the impact of competition, general agglomeration effects and overly high regional wages on local employment growth.
Keywords: 330